Coal-based solid waste negative carbon filling slurry for underground goaf and preparation method of coal-based solid waste negative carbon filling slurry

Through the preparation method of coal-based solid waste negative carbon filling slurry, the first and second stage mineralization reactions are carried out using coal gangue, fly ash and other materials, which solves the problems of low calcium content and additive pollution in fly ash, and achieves high carbon sequestration and high compressive strength ore backfill materials, meeting the requirements of green environmental protection and economic benefits.

CN119841614AActive Publication Date: 2025-04-18CHINA UNIV OF MINING & TECH

Patent Information

Application Number
CN202510062464.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

In the prior art, fly ash has a low calcium content, fly ash alone is used as backfilling material, the compressive strength and carbon sequestration of the test piece are lower, and excessive additives may contaminate groundwater.

Method used

The coal-based solid waste negative carbon filling slurry is used, consisting of coal gangue, fly ash, carbon fixing materials, cement, water glass and alkali exciters. Through the first and second stage mineralization reactions, CO2 is further absorbed, and the carbon fixing amount and compressive strength are increased.

Benefits of technology

The carbon fixation amount and compressive strength are improved, and the carbon fixation amount is as high as 65.6kg CO2/t coal-based solid waste, and the compressive strength reaches 5.6MPa, which meets the strength requirements of mine backfill materials, while reducing costs and not contaminating groundwater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841614A_ABST
    Figure CN119841614A_ABST
Patent Text Reader

Abstract

The invention discloses coal-based solid waste negative carbon filling slurry for an underground goaf and a preparation method of the coal-based solid waste negative carbon filling slurry. The coal-based solid waste negative carbon filling slurry is prepared from the following components in percentage by mass: 60-65% of coal gangue, 18-22% of fly ash, 9-12% of a carbon sequestration material, 5-9% of cement, 0.5-1.5% of water glass and 0.1-0.5% of an alkali activator. The carbon sequestration amount and compressive strength of the material are improved by adjusting the water cement ratio, the solid waste ratio and the additive ratio, the prepared slurry has certain fluidity and can be conveyed to a mine pit goaf through a pipeline, the carbon sequestration amount of the slurry reaches up to 65.6 kg CO2 / t coal-based solid waste, the compressive strength of a test piece reaches up to 5.6 MPa after the slurry is solidified, and the strength requirement of the mine pit backfill material can be met. The preparation method is low in cost, and the prepared slurry does not pollute underground water resources, is green and environment-friendly, and has a remarkable carbon sequestration effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coal-based solid waste mineralization and CO2 storage and mine goaf filling, and in particular to a coal-based solid waste negative carbon filling slurry for underground goaf and a preparation method thereof. Background Art

[0002] The dual carbon goals have placed crucial new demands on the transformation, upgrading, and green, low-carbon development of the coal industry. Currently, the coal-dominated energy structure and high-intensity coal mining have led to the massive accumulation of solid waste in mining areas. This not only significantly occupies land space, but also exacerbates ecological damage and emits large amounts of greenhouse gases. This has become a major obstacle to the coal industry's green, low-carbon development. Facing this challenge, adhering to the principles of "utilizing waste to sequester carbon, and recycling and regenerating" requires the urgent exploration of new disposal pathways for coal mining solid waste that are harmless, reduced in volume, resource-based, and low-carbon. At the same time, innovative development of efficient mining solid waste disposal technologies, fully utilizing underground space in goafs, and integrating them with CO2 capture, utilization, and storage (CCUS) technology have become urgent needs for my country's mining areas to promote green, low-carbon development under the dual carbon goals.

[0003] The patent with publication number CN202311355402.9 discloses a method for constructing an internal spoil dump based on a carbon dioxide reservoir using fly ash-based cementitious materials. This method utilizes the cementitious properties of fly ash from pit-mouth coal-fired power plants to prepare ultra-high-dosage fly ash-based cementitious materials. The carbon dioxide reservoir is constructed using high-strength fly ash-based cementitious materials, and the open-pit mine is backfilled with cement-free low-strength fly ash-based cementitious materials, thereby realizing the resource utilization and efficient coordinated disposal of fly ash solid waste.

[0004] Patent publication number CN114133170A discloses a mine backfill material, preparation method, and application thereof. The mine backfill material is composed of the following raw materials in parts by weight: 25-30 parts industrial solid waste, 170-210 parts water, 1-3 parts sodium dodecylbenzene sulfonate, 1-5 parts polyvinyl alcohol, and 8-12 parts cement. The preparation method comprises: S1, pulverizing the industrial solid waste; S2, hydrating and calcining the raw materials obtained in step S1 with a portion of water; S3, mixing the sample obtained in step S2 with sodium dodecylbenzene sulfonate, polyvinyl alcohol, and the remaining water to form a slurry, and then injecting carbon dioxide for mineralization; S4, mixing the mineralized sample obtained in step S3 with cement. The filler of this invention can be used for backfilling coal mines, reducing backfill costs and having the dual advantages of reducing carbon dioxide emissions and solving the problem of industrial waste discharge.

[0005] However, fly ash typically contains low levels of calcium, and specimens made solely of fly ash as backfill material exhibit low compressive strength and carbon sequestration. While adding excessive additives to pit backfill can improve specimen strength, adding organic additives carries the risk of groundwater contamination. Summary of the Invention

[0006] The purpose of the present invention is to provide a coal-based solid waste negative carbon filling slurry for underground goaf and a preparation method thereof, which can reduce costs, and the prepared filling slurry can increase the carbon content and compressive strength.

[0007] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0008] A coal-based solid waste negative carbon filling slurry for underground goaf is prepared from the following components in percentage by mass: 60% to 65% of coal gangue as coarse aggregate, 18% to 22% of fly ash as fine aggregate, 9% to 12% of carbon-fixing material, 5% to 9% of cement as gelling material, 0.5% to 1.5% of water glass as a coagulant, and 0.1% to 0.5% of an alkali activator; the carbon-fixing material is one of carbide slag, slaked lime, and quicklime; and the alkali activator is sodium hydroxide or potassium hydroxide.

[0009] Preferably, the fly ash particle size is less than 0.075 mm.

[0010] To achieve the above-mentioned object of the invention, the present invention also provides a method for preparing the coal-based solid waste negative carbon filling slurry in the above-mentioned underground goaf, comprising the following steps:

[0011] S1. Grinding the coal gangue to obtain coal gangue particles with a particle size of 2 to 5 mm as inert aggregate; ball-milling the fly ash to less than 0.075 mm;

[0012] S2, first stage mineralization: weigh carbide slag, slaked lime or quicklime according to the formula and add them into the reactor, then add water according to a certain water-cement ratio and stir to obtain the slurry required for the first stage mineralization, and introduce CO2 into the reactor to cause the first stage mineralization reaction;

[0013] S3, second stage mineralization: add fly ash according to the formula amount to the slurry generated after the first stage mineralization reaction, stir and react to obtain the second stage mineralization slurry;

[0014] S4. Add coal gangue, alkali activator, water glass and cement to the second stage mineralization slurry according to the formula, further stir in the reactor, and wait until the slurry is evenly mixed to obtain the filling slurry.

[0015] Preferably, in step S2, the water-cement ratio is 0.325-0.375.

[0016] Preferably, in step S2, the temperature, pressure and reaction time of the first stage of mineralization are 20-35° C., 0.5-2 MPa and 15-30 min respectively.

[0017] Preferably, in step S3, the temperature, pressure and reaction time of the second stage mineralization are 20-35° C., 0.4-1 MPa and 15-30 min, respectively.

[0018] Preferably, in step S2, the CO2 comes from a carbon capture device in a coal-fired power plant and has a purity higher than 98%.

[0019] In the present invention, gangue serves as coarse aggregate and mainly plays a supporting role; fly ash serves as fine aggregate and contains CaO with mineralization reaction activity. The addition of fly ash can further absorb the CO2 remaining from the first-stage mineralization reaction to increase the carbon fixation amount; the alkali activator and cement play a gelling role, connecting fly ash and gangue and other coarse and fine aggregates, thereby improving the compressive strength of the slurry after solidification; water glass can shorten the coagulation time of the slurry and play a coagulant role; using carbide slag, quicklime or slaked lime as carbon-fixing materials can capture CO2 at a low cost, and combined with mineralization and curing technology, it can further improve the strength of the specimen. In addition, in the present invention, the first-stage mineralization is the main carbon fixation link; the second-stage mineralization can further absorb the remaining CO2; finally, the slurry is transported to the mine goaf for the third-stage mineralization. This stage is the link to improve the compressive strength of the backfill material. In this link, coarse aggregate, gelling agent, alkali activator and coagulant are added to the slurry so that the compressive strength of the slurry reaches 3MPa after solidification.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] This method improves the carbon sequestration and compressive strength of the material by adjusting the water-cement ratio, the solid waste ratio, and the additive ratio. The resulting slurry has a certain degree of fluidity and can be transported to the mine goaf through a pipeline. It can capture up to 65.6kg CO₂ / t of coal-based solid waste. After the slurry solidifies, the compressive strength of the test specimen reaches 5.6MPa, which can meet the strength requirements of mine backfill materials. This method is low-cost, and the resulting slurry does not pollute groundwater resources. It is environmentally friendly and has a significant carbon sequestration effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a mineralized CO2 pressure drop diagram for Example 1;

[0023] Figure 2 This is the CO2 pressure drop diagram for the second stage mineralization of Example 1;

[0024] Figure 3 This is a diagram of the three-stage mineralization curing specimen of Example 1. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to specific embodiments.

[0026] Example 1

[0027] A coal-based solid waste negative carbon filling slurry for underground goaf is prepared from the following components in percentage by mass: 63% coal gangue as coarse aggregate, 22% fly ash as fine aggregate, 9% quicklime as carbon-fixing material, 5% cement as gelling material, 0.5% water glass as coagulant, and 0.5% NaOH as alkali activator; the fly ash particle size is less than 0.075 mm.

[0028] The method for preparing the coal-based solid waste negative carbon filling slurry in the underground goaf includes the following steps:

[0029] S1. Ball-mill the fly ash to 0.075 mm and crush the coal gangue to a particle size of 2 to 5 mm;

[0030] S2, weighed quicklime (9g) is placed in a reactor according to the water-cement ratio (0.325) of the total material, the reactor speed is adjusted to 900rpm, CO2 is introduced into the reactor, the pressure in the reactor is 1.2MPa, and the reaction time is 30min to obtain a mineralized slurry;

[0031] S3. Add fine aggregate (22 g of fly ash) to the slurry obtained from the first-stage mineralization according to the proportion of ingredients, and further stir at 900 rpm for 30 min. The pressure in the reactor is about 0.4 MPa, and the reaction time is 30 min. The CaO with mineralization reaction activity in the fly ash further absorbs the CO2 remaining from the first-stage mineralization reaction to obtain a second-stage mineralization slurry;

[0032] S4. Add coarse aggregate (63 g of coal gangue), 5 g of cement, 0.5 g of water glass, and 0.5 g of sodium hydroxide to the prepared second-ore mineralization slurry according to the proportion of ingredients, and stir evenly to obtain a mine filling slurry.

[0033] The slurry was naturally cured for 7 days, and then the temperature, humidity and pressure in the underground goaf environment were simulated and mineralized for 72 hours to finally obtain the mine filling material. The CO2 fixed in the first and second stage mineralization stages are shown in Table 1. The compressive strength of the mine backfill material after the slurry solidified and cured is shown in Table 1. The CO2 pressure drop diagrams of the first and second stage mineralization are shown in Table 1. Figure 1-2 As shown, the specimens after the slurry solidified after the first and second stage mineralization are as follows Figure 3 shown.

[0034] Example 2

[0035] A coal-based solid waste negative carbon filling slurry for underground goaf is prepared from the following components in percentage by mass: 64% coal gangue as coarse aggregate, 20% fly ash as fine aggregate, 9% quicklime as carbon-fixing material, 5.4% cement as gelling material, 1.5% water glass as coagulant, and 0.1% NaOH as alkali activator; the fly ash particle size is less than 0.075 mm.

[0036] The method for preparing the coal-based solid waste negative carbon filling slurry in the underground goaf includes the following steps:

[0037] S1. Ball-mill the fly ash to 0.075 mm and crush the coal gangue to a particle size of 2 to 5 mm;

[0038] S2, weighed quicklime (9g) is placed in a reactor according to the water-cement ratio (0.325) of the total material, the reactor speed is adjusted to 900rpm, CO2 is introduced into the reactor, the pressure in the reactor is 1.2MPa, and the reaction time is 30min to obtain a mineralized slurry;

[0039] S3. Add fine aggregate (20 g of fly ash) to the slurry obtained from the first-stage mineralization according to the proportion of ingredients, and further stir at 900 rpm for 30 min. The pressure in the reactor is about 0.4 MPa, and the reaction time is 30 min. The CaO with mineralization reaction activity in the fly ash further absorbs the CO2 remaining in the first-stage mineralization reaction to obtain a second-stage mineralization slurry;

[0040] S4. Add coarse aggregate (64 g of coal gangue), 5.4 g of cement, 1.5 g of water glass, and 0.1 g of sodium hydroxide to the prepared second-ore mineralization slurry according to the proportion of ingredients, and stir evenly to obtain a mine filling slurry.

[0041] The slurry was naturally cured for 7 days, and then mineralized and cured for 72 hours under the simulated temperature, humidity and pressure conditions of the underground goaf environment to finally obtain the pit filling material. The CO2 fixed in the first and second mineralization stages is shown in Table 1. The compressive strength of the pit backfill material after the slurry solidified and cured is also shown in Table 1.

[0042] Example 3

[0043] A coal-based solid waste negative carbon filling slurry for underground goaf is prepared from the following components in percentage by mass: 65% coal gangue as coarse aggregate, 18% fly ash as fine aggregate, 9% slaked lime as carbon-fixing material, 7% cement as gelling material, 0.9% water glass as coagulant aid, and 0.1% NaOH as alkali activator; the fly ash particle size is less than 0.075 mm.

[0044] The method for preparing the coal-based solid waste negative carbon filling slurry in the underground goaf includes the following steps:

[0045] S1. Ball-mill the fly ash to 0.075 mm and crush the coal gangue to a particle size of 2 to 5 mm;

[0046] S2, weighed slaked lime is placed in a reactor according to the water-cement ratio (0.35) of the total material, the reactor speed is adjusted to 900 rpm, CO2 is introduced into the reactor, the pressure in the reactor is 1.2 MPa, and the reaction time is 30 min to obtain a mineralized slurry;

[0047] S3. Add fine aggregate (18 g of fly ash) to the slurry obtained from the first-stage mineralization according to the proportion of ingredients, and further stir at 900 rpm for 30 min. The pressure in the reactor is about 0.4 MPa, and the reaction time is 30 min. The CaO with mineralization reaction activity in the fly ash further absorbs the CO2 remaining in the first-stage mineralization reaction to obtain a second-stage mineralization slurry;

[0048] S4. Add coarse aggregate (65 g of coal gangue), 7 g of cement, 0.9 g of water glass, and 0.1 g of sodium hydroxide to the prepared second-ore mineralization slurry according to the proportion of ingredients, and stir evenly to obtain a mine filling slurry.

[0049] The slurry was naturally cured for 7 days, and then mineralized and cured for 72 hours under the simulated temperature, humidity and pressure conditions of the underground goaf environment to finally obtain the pit filling material. The CO2 fixed in the first and second mineralization stages is shown in Table 1. The compressive strength of the pit backfill material after the slurry solidified and cured is also shown in Table 1.

[0050] Example 4

[0051] A coal-based solid waste negative carbon filling slurry for underground goaf is prepared from the following components in percentage by mass: 60% coal gangue as coarse aggregate, 22% fly ash as fine aggregate, 9% carbide slag as carbon-fixing material, 8% cement as gelling material, 0.9% water glass as coagulant aid, and 0.1% NaOH as alkali activator; the fly ash particle size is less than 0.075 mm.

[0052] The method for preparing the coal-based solid waste negative carbon filling slurry in the underground goaf includes the following steps:

[0053] S1. Ball-mill the fly ash to 0.075 mm and crush the coal gangue to a particle size of 2 to 5 mm;

[0054] S2, weighed quicklime (9g) is placed in a reactor according to the water-cement ratio (0.35) of the total material, the reactor speed is adjusted to 900rpm, CO2 is introduced into the reactor, the pressure in the reactor is 1.2MPa, and the reaction time is 30min to obtain a mineralized slurry;

[0055] S3. Add fine aggregate (22 g of fly ash) to the slurry obtained from the first-stage mineralization according to the proportion of ingredients, and further stir at 900 rpm for 30 min. The pressure in the reactor is about 0.4 MPa, and the reaction time is 30 min. The CaO with mineralization reaction activity in the fly ash further absorbs the CO2 remaining from the first-stage mineralization reaction to obtain a second-stage mineralization slurry;

[0056] S4. Add coarse aggregate (60 g of coal gangue), 8 g of cement, 0.9 g of water glass, and 0.1 g of sodium hydroxide to the prepared second-ore mineralization slurry according to the proportion of ingredients, and stir evenly to obtain a mine filling slurry.

[0057] The slurry was naturally cured for 7 days, and then mineralized and cured for 72 hours under the simulated temperature, humidity and pressure conditions of the underground goaf environment to finally obtain the pit filling material. The CO2 fixed in the first and second mineralization stages is shown in Table 1. The compressive strength of the pit backfill material after the slurry solidified and cured is also shown in Table 1.

[0058] Example 5

[0059] A coal-based solid waste negative carbon filling slurry for underground goaf is prepared from the following components in percentage by mass: 61% coal gangue as coarse aggregate, 20% fly ash as fine aggregate, 9% carbide slag as carbon-fixing material, 9% cement as gelling material, 0.9% water glass as a coagulant, and 0.1% NaOH as a gelling material; the fly ash particle size is less than 0.075 mm.

[0060] The method for preparing the coal-based solid waste negative carbon filling slurry in the underground goaf includes the following steps:

[0061] S1. Ball-mill the fly ash to 0.075 mm and crush the coal gangue to a particle size of 2 to 5 mm;

[0062] S2, weighed carbide slag (9g) was placed in a reactor according to the water-cement ratio of the total material (0.375), the reactor speed was adjusted to 900rpm, CO2 was introduced into the reactor, the pressure in the reactor was 1.2MPa, and the reaction time was 30min to obtain a mineralized slurry;

[0063] S3. Add fine aggregate (20 g of fly ash) to the slurry obtained from the first-stage mineralization according to the proportion of ingredients, and further stir at 900 rpm for 30 min. The pressure in the reactor is about 0.4 MPa, and the reaction time is 30 min. The CaO with mineralization reaction activity in the fly ash further absorbs the CO2 remaining in the first-stage mineralization reaction to obtain a second-stage mineralization slurry;

[0064] S4. Add coarse aggregate (61 g of coal gangue), 9 g of cement, 0.9 g of water glass, and 0.1 g of sodium hydroxide to the prepared second-ore mineralization slurry according to the proportion of ingredients, and stir evenly to obtain a mine filling slurry.

[0065] The slurry was naturally cured for 7 days, and then mineralized and cured for 72 hours under the simulated temperature, humidity and pressure conditions of the underground goaf environment to finally obtain the pit filling material. The CO2 fixed in the first and second mineralization stages is shown in Table 1. The compressive strength of the pit backfill material after the slurry solidified and cured is also shown in Table 1.

[0066] Table 1 Test results of mineralized curing concrete solid bricks in Examples 1 to 5

[0067] Example Compressive strength (MPa) Carbon sequestration (kg / t) 1 3.76 65.60 2 3.94 65.57 3 4.31 65.54 4 5.12 64.55 5 5.66 64.53

[0068] from Figure 1 and Figure 2 It can be seen that the first and second stage mineralization reactions are completed within 10 minutes, and the reaction rate is fast. After calculation, the carbon fixation amount of the first stage mineralization within 10 minutes is 64.1g, the carbon fixation amount of the second stage mineralization is 1.5g, and the total carbon fixation amount is 65.6g / t. The specimen after the slurry solidifies after the first and second stage mineralization is as follows Figure 3 As shown in the figure, after pressure testing, the compressive strength is 3.76 MPa, and as the amount of cement added increases, the compressive strength increases, as shown in Example 2 and Example 3. In Example 4 and Example 5, slaked lime or carbide slag is used as the carbon-fixing material, and the main component of carbide slag is Ca(OH)2, and the carbon-fixing capacity also reaches 64.5 kg / t.

[0069] As can be seen from Table 1, the carbon fixation capacity of the slurry prepared by the present invention is as high as 65.6 kg CO2 / t coal-based solid waste, and the compressive strength of the specimen after the slurry solidifies is as high as 5.66 MPa, which can meet the strength requirements of mine backfill materials.

[0070] In combination with the above embodiments, the formula ratio and preparation method of the present invention are described in detail. The present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, the ratio of the formula of each stage of the three-stage mineralization of the present invention can be adjusted, which all belong to the scope of protection of the present invention.

Claims

1. A coal-based solid waste negative carbon filling slurry for underground goaf, characterized in that: The invention is prepared from the following components in percentage by mass: 60% to 65% of coal gangue as coarse aggregate, 18% to 22% of fly ash as fine aggregate, 9% to 12% of carbon-fixing material, 5% to 9% of cement as gelling material, 0.5% to 1.5% of water glass as coagulant aid, and 0.1% to 0.5% of alkali activator; the carbon-fixing material is one of carbide slag, slaked lime, and quicklime; and the alkali activator is sodium hydroxide or potassium hydroxide.

2. The coal-based solid waste negative carbon filling slurry for underground goaf according to claim 1, characterized in that: The particle size of the fly ash is less than 0.075 mm.

3. A method for preparing the coal-based solid waste negative carbon filling slurry in underground goaf as claimed in claim 1, characterized in that: The following steps are involved: S1. Grinding coal gangue to obtain coal gangue particles with a particle size of 2 to 5 mm as inert aggregate; ball-milling fly ash to less than 0.075 mm; S2, primary mineralization: weigh carbide slag, slaked lime or quicklime according to the formula and add them into the reactor, then add water according to a certain water-cement ratio and stir to obtain the slurry required for primary mineralization, and introduce CO2 into the reactor to cause a primary mineralization reaction; S3, second stage mineralization: add fly ash according to the formula amount to the slurry generated after the first stage mineralization reaction, stir and react to obtain the second stage mineralization slurry; S4. Add coal gangue, alkali activator, water glass and cement into the second-stage mineralization slurry according to the formula, further stir in the reactor, and obtain filling slurry after the slurry is evenly mixed.

4. The method for preparing a coal-based solid waste negative carbon filling slurry in underground goaf according to claim 3, characterized in that: In step S2, the water-cement ratio is 0.325-0.

375.

5. The method for preparing a coal-based solid waste negative carbon filling slurry in underground goaf according to claim 3 or 4, characterized in that: In step S2, the temperature, pressure and reaction time of a mineralization stage are 20-35°C, 0.5-2MPa and 15-30min respectively.

6. The method for preparing a coal-based solid waste negative carbon filling slurry in underground goaf according to claim 3 or 4, characterized in that: In step S3, the temperature, pressure and reaction time of the second stage mineralization are 20-35°C, 0.4-1 MPa and 15-30 min respectively.

7. The method for preparing a coal-based solid waste negative carbon filling slurry for underground goaf according to claim 3 or 4, characterized in that: In step S2, CO2 comes from a carbon capture device in a coal-fired power plant, and has a purity of more than 98%.

Citation Information

Patent Citations

  • Carbon negative material

    CN103239971A

  • Carbonated coal gangue-based paste as well as preparation method and application thereof

    CN115108763A

  • Mine solid waste fluidization filling treatment and carbon dioxide sealing method

    CN115628106A

  • Post-rack paste CGIF material and negative carbon filling mining method

    CN118239744A

  • Integrated method for mineralizing and sequestrating carbon dioxide and filling goaf with fly ash

    US20230358136A1

Cited By

  • Amino acid mediated coal-based solid waste negative carbon filling material and preparation method thereof

    CN120923173A

  • Preparation method of coal-based solid waste negative carbon filling material for coal mine goaf

    CN121517176A